Construction of a bone-like surface layer on hydroxyl-modified carbon/carbon composite implants via biomimetic mineralization and in vivo tests. Issue 11 (25th January 2016) - Cao, Ning; Yang, Zhenguo; Yang, Bai; Wang, Wenbo; Boukherroub, Rabah; Li, Musen
Abstract : By means of biomimetic mineralization method, Mg-doped hydroxyapatite nano particles were successfully prepared on hydroxyl-modified C/C surfaces. Abstract : Carbon/carbon composites, solely composed of pure carbon, are typical fiber fabric reinforced porous composites. They have been widely studied due to their excellent bio-inert performance and mechanical properties. However, their applications are restricted by two problems, i.e., easy dissociation of surface carbon particles and poor wettability of common bioactive coatings on their surface. To overcome these problems, we have adopted a biomimetic mineralization method, where Mg-doped hydroxyapatite particles were successfully prepared on hydroxyl-modified C/C surfaces, prepared via HNO3 oxidation. In this way, the original porous morphology of C/C, which is conducive to cell proliferation, is well-preserved. In the meanwhile, the introduction of electrochemical methods sped up the process of bio-mineralization and facilitated the construction of bone-like surface layers. In vivo tests revealed that 90 days after implantation for bone defect repair, the resulting C/C displayed unprecedented surface chemical stability and biocompatibility.